Global functional genomics reveals GRK5 as a cystic fibrosis therapeutic target synergistic with current modulators - Hugo M. Botelho; Miquéias Lopes-Pacheco; Madalena C. Pinto; Violeta Railean; Ines Pankonien; Mariana F. Caleiro; Luka A. Clarke; Vasco Cachatra; Beate Neumann; Christian Tischer; Cristina Moiteiro; Jiraporn Ousingsawat; et al. (iScience)
Summary: Cystic fibrosis (CF) is a life-shortening disease affecting >160,000 individuals worldwide predominantly with respiratory symptoms. About 80% of individuals with CF have the p.Phe508del variant that causes the CF transmembrane conductance regulator (CFTR) protein to misfold and be targeted for premature degradation by the endoplasmic reticulum (ER) quality control (ERQC), thus preventing its plasma membrane (PM) traffic. Despite the recent approval of a “highly effective” drug rescuing p.Phe508del-CFTR, maximal lung function improvement is ∼14%. To identify global modulators of p.Phe508del traffic, we performed a high-content small interfering RNA (siRNA) microscopy-based screen of >9,000 genes and monitored p.Phe508del-CFTR PM rescue in human airway cells. This primary screen identified 227 p.Phe508del-CFTR traffic regulators, of which 35 could be validated by additional siRNAs. Subsequent mechanistic studies established GRK5 as a robust regulator whose inhibition rescues p.Phe508del-CFTR PM traffic and function in primary and immortalized cells, thus emerging as a novel potential drug target for CF.